DAMPAK PEMBANGUNAN JALAN BARU TERHADAP SOSIAL EKONOMI MASYARAKAT DI DESA SAUREINU KECAMATAN SIPORA SELATAN KABUPATEN KEPULAUAN MENTAWAI - Ristawani, Ristawani; Erita, Yeni; Keslan, Widya Prari (STKIP PGRI Sumbar, 2013)
This study aims to determine the impact of socio-economic development of the community roads in the Village Saureinu Sipora Selatan District Mentawai Islands Region, seen from: 1) education, 2) the level of health, 3) livelihood and 4) income.This research is descriptive. The population in this study are all the people in the Saureinu village of 343 families (KK). Sample area is Sawahan hamlet, hamlet Kaliou, Sikirene hamlet. Sampling is important in the study because of the large number of population in the study. Samples were taken with a random sampling method proportional to the proportion of 50% so that the sample was 87 families.The research found that: 1) the level of public education before the new way in the Village Saureinu Sipora Selatan District Mentawai Islands Region, better educational facilities as no new roads, (2) public health in the Village Saureinu Sipora Selatan District Mentawai Islands Region before and after the new road, (3) The occupation of the people in the Village Saureinu Sipora Selatan District Mentawai Islands Region before and after the new road is generally no different, as the most basic type of business are farmers and do not have a side business, and (4) Income before society presence in the Village Saureinu Sipora Selatan District Mentawai Islands Region is lower than the income of the people in the village after the district Saureinu South Sipora Mentawai Islands